2018
DOI: 10.1536/ihj.17-610
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Dysfunction Is Associated with Cognitive Impairment of Elderly Cardiovascular Disease Patients

Abstract: Cognitive impairment is frequently represented in elderly patients with cardiovascular disease (CVD); yet, the mechanism is uncertain. Recent studies have suggested the association between the vascular endothelial dysfunction and cognitive impairment. The aim of this study was to clarify the association between endothelial dysfunction and cognitive impairment in elderly patients with CVD.A total of 80 elderly patients (> 70 years old) with CVD were included. Patients who had already pharmacologically intervene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…As a common feature of various diseases, cognitive impairment impacts the health of elderly patients (52). Previous studies showed that BBB permeability has an essential effect on cognitive impairment-related diseases (53), but the function and mechanism of BBB permeability in cognitive impairment caused by sleep deprivation is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…As a common feature of various diseases, cognitive impairment impacts the health of elderly patients (52). Previous studies showed that BBB permeability has an essential effect on cognitive impairment-related diseases (53), but the function and mechanism of BBB permeability in cognitive impairment caused by sleep deprivation is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The strong relationship between proBNPage and cardiovascular pathologies leads to the conclusion that the presence of these pathologies may also have a strong influence on the self-rating of health status. With the intermediation of endothelial dysfunction, hypertension is a relevant cause of cardiovascular damage, and both hypertension and endothelial dysfunction have been found to be associated with cognitive impairment [56,57]. The impact on cognitive aging of even subtle alterations of cardiovascular hemodynamics, including both cardiac output and arterial stiffening, has recently been reviewed [58].…”
Section: Psychological or Mental Complaintsmentioning
confidence: 99%
“…Before the evaluation, the patients were asked to rest for 30 minutes in the supine position in a quiet, dark, air-conditioned room (22 -25 ). 12) The FMD procedure was performed in the morning or evening (between 6 and 8 am or between 5 and 6 pm). A forearm cuff was then inflated for 5 minutes at 50 mmHg above the systolic blood pressure just before the FMD measurement.…”
Section: Study Populationmentioning
confidence: 99%